Pengaruh Sektor Pariwisata Terhadap Pendapatan Asli Daerah di Kota Padang - Lestari, Novita; Idris, Idris (Universitas Negeri Padang, 2024)
Anagement of government and development handed over to local governments and seek sources of financing in carrying out this management. One of the sectors that has the potential to become the highest source of PAD is the tourism sector. The purpose of this study was to determine the effect of the number of tourist visits, the number of hotels, the amount of spending on the development of the tourism sector on local revenue in the city of Padang in 1990-2019. In this study using 2 variables, namely the dependent variable and independent variable. The dependent variable is local revenue (Y) and the independent variable is the number of tourist visits (X1), the number of hotels (X2), the amount of tourism sector development spending (X3). The data used is secondary data obtained from the Padang City Central Statistics Agency (BPS), the Padang City Tourism Office and other literature such as books and economic journals. The analytical tool used is multiple linear regression and processed with eviews 12. The results of the study show that there is an influence on the number of tourists on regional original income in the city of Padang. There is no effect of the number of hotels on local revenue in the City of Paadang. There is an influence on the amount of spending on the development of the tourism sector on local revenue in the city of Padang. There is an influence on the number of tourist visits and the amount of tourism sector development spending on local revenue in the city of Padang.